The Opinions of School Counselors on Teacher Behaviors towards Students with Special Needs Inclusive Classrooms - LEVENT, AHMET FARUK (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2020)
The purpose of this study was to examine the opinions of school counselors on teacher behaviors towards students with special needs in inclusive classrooms. This study was carried out with a phenomenological design, which is one of the qualitative research methods, and the data of the study were obtained by face-to-face interviews and by a semi-structured interview form. Within the scope of the research, 20 school counselors working in different school types were interviewed. The data obtained were coded under themes and subjected to content analysis. According to the opinions of school counselors, teachers (branch teachers) generally do not pay due attention to to individualized education plans (IEP) for students with special needs and regard this as unnecessary workload. However, school counselors stated that teachers do not have sufficient information in order to recognize students with special needs and that their special education and inclusive knowledge is insufficient. They also stated that teachers did not want students with special needs in the classroom and they caused that these students felt rejected. School counselors suggested that in-service training programs should be organized to prevent negative teacher behaviors at schools.
Keywords: Inclusive classrooms; school; teacher; students with special needs; school counselors; special education; ATTITUDES; EDUCATION; EXPERIENCE; PEERS